Time Series Forecasting Covid 19 in Indonesia with a Perceptron Multilayer Neural Network - Reynaldi Thimotius Abineno (JURNAL TEKNIK INFORMATIKA INOVATIF WIRA WACANA, 2023)
Covid 19, which was first discovered in Wuhan, China, spread so rapidly throughout the world in early 2020 to date, according to data to date, the death rate due to Covid 19 has reached 1,338,100 people from a total of 55,624,562 positive cases worldwide. Prevention needs to be done to inhibit the rate of positive cases of Covid which are still increasing today. one of the efforts that can be done is to make predictions or forecasts. In this study, prediction or forecasting of positive cases of Covid will be carried out using time series data in the last few months using the backpropagation neural network method or multi-layer perceptron modeling to produce predictions with fairly good accuracy.